The Coordination of Domestic Public Debt and Monetary Management in Economies in Transition : Issues and Lessons From Experience. (IMF Working Papers; Working Paper ;, 1994)
In economies in transition, the development of financial markets is a common objective linking the monetary and fiscal authorities, while monetary and public debt management cannot be strictly separated. This calls for close coordination of objectives and instruments of monetary and debt management, and the development of supporting institutional and operational arrangements. Key aspects of these arrangements are surveyed.